Tackling Dialysis Burden around the World: A Global Challenge - Philip Kam-Tao Li; Gordon Chun-Kau Chan; Jianghua Chen; Hung-Chun Chen; Yuk-Lun Cheng; Stanley L.-S. Fan; John Cijiang He; Weixin Hu; Wai-Hon Lim; York Pei; Boon Wee Teo; Ping Zhang; et al. (Karger Publishers, 2021)
CKD is a global problem that causes significant burden to the healthcare system and the economy in addition to its impact on morbidity and mortality of patients. Around the world, in both developing and developed economies, the nephrologists and governments face the challenges of the need to provide a quality and cost-effective kidney replacement therapy for CKD patients when their kidneys fail. In December 2019, the 3rd International Congress of Chinese Nephrologists was held in Nanjing, China, and in the meeting, a symposium and roundtable discussion on how to deal with this CKD burden was held with opinion leaders from countries and regions around the world, including Australia, Canada, China, Hong Kong, Singapore, Taiwan, the UK, and the USA. The participants concluded that an integrated approach with early detection of CKD, prompt treatment to slow down progression, promotion of home-based dialysis therapy like peritoneal dialysis and home HD, together with promotion of kidney transplantation, are possible effective ways to combat this ongoing worldwide challenge.